O processo de socialização da questão da habitação: o Residencial Rio Anil Camboa - OLIVEIRA, Maysa Mayara Costa de (2016)
This thesis has for intention the process of socialization in the new habitation of people who have to live in the Residential Rio Anil Cambodia, built by PAC (Development Acceleration Program), federal government initiative situated on Camboa, central popular district of city São Luís, Maranhão. With the implementation this program, the PAC Rio Anil was aimed to remove the precarious habitation forms who were in the left bank the river Anil, especially the stilts. Started in 2007, the project involves these houses the neighborhoods Alemanha, Fé em Deus, Liberdade and Camboa, having built three residences to house these families: Residential Jackson Lago, Residential Rio Anil Camboa and Residential Monte Castelo. First residential inaugurated by PAC, delivered in 2009, the Rio Anil Camboa houses on 288 apartments, divided in 18 blocks, the families from various "slums" integreted old space the stilts houses of neighborhoods that bordering the Anil river. However, the significant change of the precarious and unhealthy housing for residential not without problems or conflicts, expressed in current socialization processes. One of these conflicts, for example, residents impute to "mix of slums," as the meeting of people from different neighborhoods made it difficult to establish links between them. Also, something verbalized often residents feel stigmatized and victims of prejudice, since the home is known as "Carandiru", the former prison of the city of São Paulo. This reality, complex object of study, makes the present work has the purpose to understand to what extent the living modes of residents are affected by a new form of housing and the way of how they construct their spatial and social relations in a new space for interaction.